Positividad de la detección molecular de malaria usando muestras de saliva humana en la región Loreto - Bocanegra Maldonado, Oliver Anthony (2022)
The microscopic and molecular diagnoses of malaria require the extraction of blood samples, which generates difficulties and rejection of this procedure in the vulnerable population to this parasitosis. In this sense, it was proposed to determine the assessability of the molecular diagnosis of malaria using human saliva samples and to compare the sensitivity and specificity with the gold standard based on PCR of blood samples. Sixty-five blood and saliva samples were collected from patients with vivax malaria, falciparum malaria and negatives, from the communities of Zungarococha (n=11), Nina Rumi (n=17), Llanchama (n=28) and Puerto Almendra (n =9), located in the southern of Iquitos, Perú. DNA from both types of samples was purified and analyzed using standard methods. Subsequently, three DNA amplification protocols based on the polymerase chain reaction (PCR) were used to perform the molecular diagnosis: PCR-Rubio, PCR-Snounou and PCR-Cytb. The assessability of the different PCR tests using saliva was 16.92%, 18.46% and 9.23%, respectively. In addition, the sensitivity and specificity of the tests were 28.95% and 100%; 31.57% and 100%; 15.79% and 100%, for P. vivax infections, while no assay detected P. falciparum DNA. In conclusion, with the protocols used, the saliva samples are not appropriate for the molecular diagnosis of malaria since the detection of parasite DNA and the sensitivity were very low (<19% and <32%, respectively), being necessary make improvements to the protocols.